Power allocation and control for multicarrier systems with soft decoding. - Hsuan-Jung Su (IEEE Journal on selected areas in communications)
We consider the application of multicarrier modulation in a wireless cellular network in order to enable high-data rate communication and alleviate the multipath induced intersymbol interference (ISI). In this scenario, power control becomes crucial in enhancing the spectral and power efficiency. A conventional approach of maintaining the same link quality for all the subchannels, in other words, disregarding any possible post-demodulation processing, is considered first. This approach appears to have increasing power consumption as the number of subchannels increases. It also deteriorates the power control stability and convergence properties in a multicell network. We attribute this phenomenon to lack of frequency diversity exploitation, and thus, we propose to use channel coding and soft decoding as vehicles to profit from the (frequency) diversity advantage in addition to the coding advantage. Based on the soft decoding performance bound, a power allocation and control algorithm is proposed. It is shown through simulations that the proposed algorithm improves the power efficiency as the number of subchannels increases. It also provides a better convergence property and is able to ?detect? and eliminate ill-conditioned subchannels. The advantages of using multicarrier modulation are thus reassured. Besides these enhancements, the proposed algorithm is simple and feasible in that it consists of only the traditional closed-loop power control algorithm and a target signal-to-interference ratio (SIR) reassignment at the receiver. Detailed channel information feedback from receiver to transmitter is not required